Radical Care: Seeking New and More Possible Meetings in the Shadows of Structural Violence - Kelly Gawel (Krisis, 2023)
This article attends to the intimate contradictions that differentially shape and limit caring capacities and relations in a violent world, and the embodied ethical and political transformations at the heart of learning to care otherwise. From manifestos calling for ‘universal care’ in defiance of the state-sanctioned horrors of the pandemic era, to the abolitionist politics of care developed by BLM organizers through movement building and healing, and the proliferation of mutual-aid infrastructures to meet needs and distribute resources in the face of overwhelming crisis and neglect—these examples and so many others illustrate with undeniable clarity that radical care is finally on the agenda. In what follows, I hope to contribute to this urgent conversation by pointing to how care is shaped in fundamentally contradictory ways under conditions of entrenched structural violence, and the limitations of normative frameworks when confronting this reality. To unambiguously valorize care in ethical and political life is to risk occluding the constitutive violence of existing social structures and norms, its impact on the intimacies of caring relations, and ultimately the ways that communities mobilize alternate economies and practices of care towards healing and social change. While it is crucial to value care and work for a more caring society, I claim that efforts to transform patterns of relational harm and develop new sensibilities should also be highlighted as integral components of radical caring praxis.